Future Development Possibilities of Talent Management Under The Influence of ‘Industry 4.0’ - Feng, Yuqin (My University, 2016)
As the fourth generation of industrial management, 'Industry 4.0' will generate major impact towards the business operation and the stakeholders’ cooperation. However, the study of industry 4.0 is currently mainly focused on the technical and production areas but seldom look into the impact towards people. Talent management is a relatively new research phenomenon that focuses on utilizing the top performance and most potential employee within the company. In order to clear the possible integration path of industry 4.0 in MNC and understand the influence of such industrial trend on the management of talents, this study is formed. This study presents three main research questions that focus on understanding the current status of talent management in typical technology MNC, influence way of this status towards industry 4.0 integration in MNC, and the impacts of industry 4.0 to talent management during/after its integration process. Ten semi-structured interviews are conducted to gather in-depth inside of research questions by this study. All interviewees are currently working inside the case company and served as operator/talent/line manager. The findings of this study were analyzed based on the study framework that created on the existing theories. This study found that a clear talent management strategy was missing from the case company, a typical technology driven MNC. The missing of clear talent management vision leads to the low satisfaction rate towards HR department and personal development possibility from both talents and line managers. Quality and quantity of talent within one company, the characteristics of tasks and the rely level of tasks on real-time information will create clear influence towards the industry 4.0 integration process. Key positions and demand of talents are expected to shift towards technology functions, opportunities of personal develop will become the most important factor for better retention performance, and all these changes will require more help from the HR department.
Keywords: Talent Management; Industry 4.0; Internet of Things and Services; Multination Corporations; Technology Integration; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|